CONSUMER BUYING BEHAVIOR IN GROCERY SHOPPING POST-COVID-19: THE ROLE OF SOCIAL MEDIA MARKETING, COUPON PRONENESS, PRICE DISCOUNT, AND PRODUCT BUNDLING - Andrianto Prasetya Nugroho; Etty Zuliawati; Tri Mulyani Kartini; Sang Dewi Roro Basuki (Jurnal Ekonomi, 2023)
The aim of this study is to evaluate factors affecting consumer buying behavior in grocery shopping post-covid-19 era. Empirical studies were conducted to determine the role of social media marketing, coupon proneness, price discount, and product bundling in grocery shopping. The sample was determined with 125 respondents from Indonesia with the criteria of consumers who have shopped at grocery stores in 2023 and followed their social media. The findings show that: (1) social media marketing has a positive impact on consumer buying behavior; (2) coupon proneness has no effect on consumer buying behavior; (3) price discount has a positive impact on consumer buying behavior; (4) product bundling has a positive impact on consumer buying behavior in grocery shopping. Social media marketing, price discount and product bundling are effective ways to influence consumer buying behavior during the covid-19 pandemic and after, while respondents were neutral when asked how important it was to them about coupon offers. Social media marketing, coupon proneness, price discount, and product bundling are able to explain consumer buying behavior by 61,1%.